Hydrogen storage by earth-abundant metals, synthesis and characterization of Al3FeH3.9. (October 2021) - Saitoh, Hiroyuki; Sato, Toyoto; Tanikami, Mai; Ikeda, Kazutaka; Machida, Akihiko; Watanuki, Tetsu; Taguchi, Tomitsugu; Yamamoto, Shunya; Yamaki, Tetsuya; Takagi, Shigeyuki; Otomo, Toshiya; Orimo, Shin-ichi
Graphical abstract: Highlights: A novel hydrogen storage material, Al3 FeH3.9, is synthesized from the earth-abundant metals aluminum and iron. Al3 FeH3.9 contains only metals with low hydrogen affinity, whereas other reported hydrides contain metals with high hydrogen affinity. The crystal structure of the synthesized Al3 FeD3.9 suggests that the mixing of the chemical state of hydrogen stabilizes Al3 FeH3.9 . The hydrogen content of Al3 FeH3.9 (2.9 wt%) exceeds that of conventional LaNi5 H x (1.4 wt%) and TiFeH x (1.9 wt%). Abstract: Among the various functionalities of hydrides, their use in hydrogen storage has been the most intensively studied because hydrides can store hydrogen compactly and safely. Thus, hydrides are key materials for the hydrogen economy. Here, the hydrogen storage material Al3 FeH3.9 has been synthesized from cost-effective earth-abundant metals, Fe and Al. Hydrides consisting of Al and transition metals with low hydrogen affinities are rare because such alloys are unstable. However, it is expected that appropriate mixing of the chemical states of hydrogen atoms would allow synthesis of Al-Fe hydrides. The experimentally determined crystal structure of Al3 FeD3.9 suggests realization of the mixing of the chemical state of hydrogen. Al3 FeH3.9 is more thermodynamically stable than AlH3, and it is likely that the mixing of the chemical state of hydrogen atoms is the source of increased stability. The results of this study confirm that by controlling the chemical states of hydrogen, it is possible to tune the thermodynamic stability of hydrides and thus realize novel functional hydrides.